“As protective gear began to run low, guidance on protection became looser” - Healthcare workers' perspectives on infection prevention and control during the COVID-19 pandemic - Aulanko, Ida; Nikuri, Petra; Oksanen, Lotta; Oksanen, Sampo; Lahdentausta, Laura; Pietiäinen, Milla; Paju, Susanna; Kivimäki, Anne; Pussinen, Pirkko; Geneid, Ahmed; Sanmark, Enni (Frontiers in Public Health, 2022)
Objectives The COVID-19 pandemic has posed several risk factors to healthcare workers' (HCWs') emotional distress. The purpose of the study was to enhance understanding of the experiences and feelings of HCWs during the COVID-19 pandemic, with specific reference to infection prevention and control (IPC) practices and guidance, focusing on the quality and availability of personal protective equipment (PPE), guidelines, and management. With a qualitative approach, we aimed to enable a wider narrative; to gain a more detailed understanding related to PPE use and identify experiences that can be overlooked in forced-choice questionnaires. Methods An online questionnaire was conducted among HCWs of the City of Helsinki and Helsinki University Hospital between 12.6.2020 and 5.4.2021. Altogether 1,580 HCWs participated in the study, from whom 579 shared 1,666 free-text responses. These responses were analyzed qualitatively, and the results were combined with statistical data on the participants' working conditions and backgrounds. Results We identified problems in PPE availability and changing guidelines as factors causing the most distress in the participants. Regarding availability, running out of masks and respirators emerged as the most worrying issue, and inadequate PPE was associated with the excessive workload (OR 1.51, CI 95% 1.01–2.25). The results also highlight the importance of transparent and clear communication regarding IPC instructions and guidance, and clear IPC guidance was associated with better levels of reported recovery from work (OR 1.51, CI 95% 1.06–2.14). Conclusions Our study highlights the importance of adequate PPE provision, transparent communication, clear guidance, and supportive supervisory work in this ongoing pandemic and potential new ones. We suggest more rigorous preparation, with crisis communication planning and emergency storage of PPE.